1991
DOI: 10.1007/bf01067665
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the pituitary-adrenal system in the syracuse high-and low-avoidance strains of rats (Rattus norvegicus)

Abstract: After many generations of selective breeding, rats of the high-avoidance strain (SHA) average 67% avoidance responses in a two-way shuttle box, whereas those of the low-avoidance strain (SLA) average 0%. Adrenal gland weights, both absolutely and relative to body weight, are 40-50% greater in adult SLA than SHA rats of both sexes. Females of both strains have larger adrenal glands than males. Morphometry revealed that the difference in adrenal size in adults is entirely in the three cortical zones. The strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…Furthermore, a higher neuroendocrine reactivity to stressors is observed in RLA rats than in RHA rats [6, 14, 17, 18, 43, 44]. Similar results have been obtained in Syracuse rats [9, 12].…”
Section: Roman and Syracuse Strains Of Ratssupporting
confidence: 71%
“…Furthermore, a higher neuroendocrine reactivity to stressors is observed in RLA rats than in RHA rats [6, 14, 17, 18, 43, 44]. Similar results have been obtained in Syracuse rats [9, 12].…”
Section: Roman and Syracuse Strains Of Ratssupporting
confidence: 71%
“…In accordance with their greater emotionality, SLA rats show a greater glucose response to an open-field [146]. However, SLA rats are characterized by modestly lower corticosterone response to ether stress, but much lower adrenal corticosterone content, as compared with SHA [147]. Similar results were observed after exogenous CRH administration [148].…”
Section: Selection On the Basis Of Active Avoidance Performancesupporting
confidence: 61%
“…This is of particular interest because previous studies have shown that the Brush Syracuse Low-Avoidance rats are more sensitive to chlordiazepoxide than the Syracuse High-Avoidance rats, and substantial evidence suggests that the Syracuse Low-Avoidance rats are more emotionally reactive than the Syracuse High-Avoidance rats in a variety of tasks including novelty stress, conditioned suppression, and active and passive avoidance learning (Brush et al, 1988;Flaherty & Rowan, 1989). Furthermore, the Syracuse Low-Avoidance rats have enlarged adrenal glands but have reduced corticosterone secretion compared with the Syracuse High-Avoidance rats (Brush, 1992;Brush, Isaacson, Pellegrino, Rykaszewski, & Shain, 1991;Del Paine & Brush, 1990). Thus, the previous finding from our laboratory that the Syracuse Low-Avoidance rats showed larger successive negative contrast effects than the Syracuse High-Avoidance rats, and that chlordiazepoxide was effective only in the Syracuse Low-Avoidance rats, suggested that more emotional rats show larger contrast effects and that the benzodiazepines are particularly effective in these rats.…”
Section: Discussionmentioning
confidence: 99%